Onchidium reevesii may be able to distinguish low-frequency sound to discriminate the state of tides. (3rd April 2022) - Rao, Rongcheng; Shen, Heding
ABSTRACT : In order to study how Onchidium reevesii predict tides, the cDNA encoding the precursor of the pedal peptide (Pep), a neuropeptide that plays an important role in neuromotor regulation, was cloned by RACE (Rapid Amplification of cDNA Ends) technology. Bioinformatics analysis was carried out on the sequence of the cloned cDNA. The frequency spectra of the intertidal zone were obtained and Quantitative Real-time PCR (qRT-PCR) experiments were carried out to study the connection between low-frequency sound and tidal perception. The full length of the cDNA was 1627 bp and it encodes 15 copies of Pep; The frequency spectra and qRT-PCR results suggest that O. reevesii can distinguish low-frequency sound waves (100–130 Hz) produced by tides, enabling them to avoid tidal immersion or to come out to feed after the tides falls. In this species, Pep may act as the neurotransmitter for tidal perception based on low-frequency sound signals. These experiments will provide a reference for the further study of the mechanism by which O. reevesii senses tides.